Air Electrodes for Flexible and Rechargeable Zn−Air Batteries. Issue 1 (16th October 2021) - Wang, Xiao Xia; Yang, Xiaoxuan; Liu, Hui; Han, Tao; Hu, Junhua; Li, Hongbo; Wu, Gang
Abstract : Rechargeable Zn−air batteries (ZABs) have attracted increasing attention as one of the most promising future energy power sources due to their relatively high specific energy density, environmental friendliness, safety, and low cost. In particular, flexible ZABs are desirable for portable and wearable electronic devices, in which the cathode can utilize air directly from the atmosphere with significantly enhanced energy density. Therefore, the air electrode consisting of oxygen electrocatalysts is the most critical component in flexible ZABs, significantly governing the overall battery performance and cost. This review highlights recent achievements in designing efficient oxygen electrocatalysts and air electrodes for rechargeable and flexible ZABs. First, the most significant innovations of recent battery configurations to improve flexibility and battery performance are introduced. Then, oxygen electrocatalysts developed for fabricating high‐performance air cathodes in flexible ZABs in terms of catalyst properties, unique nanostructures, and morphologies are emphasized. Furthermore, effective architectures of air electrodes are discussed to highlight structural stability and charge/mass transports for improving battery performance. Finally, a perspective for designing durable and high‐power air electrodes for flexible ZABs is provided, aiming to summarize current challenges and possible solutions to commercialize the exciting battery technology eventually. Abstract : This review summarizes recent advances in designing efficient oxygen electrocatalysts and air electrodes for rechargeable and flexible zinc−air batteries with emphasis on innovative oxygen catalysts and electrode configurations to improve flexibility, structural stability, and battery performance.